A Novel Approach to New-Onset Hemiplegic Shoulder Pain With Decreased Range of Motion Using Targeted Diagnostic Nerve Blocks: The ViVe Algorithm - Fitterer, John W.; Picelli, Alessandro; Winston, Paul (Frontiers in Neurology, 2021)
Introduction: Hemiplegic shoulder pain (HSP) is the most common pain disorder after stroke with incidence estimates of 30%-70%, and associated with reductions in function, interference with rehabilitation, and a reduced quality of life. Onset may occur as soon as a week after stroke in 17% of patients. Management of HSP represents a complex treatment pathway with a lack of evidence to support one treatment. The pain has heterogeneous causes. In the acute setting, decreased range of motion in the shoulder can be due to; early onset spasticity, capsular pattern stiffness, glenohumeral pathology, or complex regional pain syndrome (CRPS). As contracture can form in up to 50% of patients after stroke, effective management of the painful shoulder and upper limb with decreased range of motion requires assessment of each possible contributor for effective treatment. The anesthetic diagnostic nerve block (DNB) is known to differentiate spasticity from contracture and other disorders of immobility and can be useful in determining an appropriate treatment pathway. Objective: To create a diagnostic algorithm to differentiate between the causes of HSP in the stiff painful shoulder in the subacute setting, using diagnostic techniques including the Budapest Criteria for CRPS, and DNB for spasticity and pain generators. Results: Examination of each joint in the upper extremity with HSP may differentiate each diagnosis with the use of an algorithm. Pain and stiffness isolated to the shoulder may be differentiated as primary shoulder pathology; sensory suprascapular DNB or intraarticular/subacromial injection can assist in differentiating adhesive capsulitis, arthritis, or rotator cuff injury. CRPS may affect the shoulder, elbow, wrist and hand, and can be evaluated with the Budapest Criteria. Spasticity can be differentiated with the use of motor DNB. A combination of these disorders may cause HSP, and the proposed treatment algorithm may offer assistance in selecting a systematic treatment pathway.